Durability of Response to Zoledronate Treatment and Competing Mortality in Paget's Disease of Bone. (30th November 2016) - Cundy, Tim; Maslowski, Katherine; Grey, Andrew; Reid, Ian R
ABSTRACT: There has been a marked secular trend in recent decades toward patients with Paget's disease presenting at a greater age and having less extensive skeletal involvement. Over a similar time frame more potent bisphosphonates with a long duration of effect have been developed, raising the prospect of many patients needing only once in a lifetime treatment. We studied a cohort of 107 patients who had been treated with intravenous zoledronate for the first time at a mean age of 76 years. Sequential measurements of the bone turnover marker procollagen‐1 NT‐peptide (P1NP) were made for up to 10 years. By 9 years, 64% showed some loss of zoledronate effect (defined as a doubling of P1NP from the nadir value after treatment), but only 14% had a biochemical relapse (defined as a P1NP value >80 μg/L). The mortality rate was substantially greater than the relapse rate—by 10 years more than half the cohort had died ( p < 0.0001). We conclude that for the majority of older people with Paget's disease a single intravenous infusion of zoledronate will provide disease suppression for the remainder of their lives. © 2016 American Society for Bone and Mineral Research. Abstract : The potent, long‐acting, bisphosphonate zoledronate is now commonly used in the treatment of Paget's disease, but contemporary patients tend to present later in life and to have fewer bones involved than formerly. This work reports that up to 10 years after zoledronate treatment, patients with Paget's disease are nearly four times more likely to die (competing mortality) than suffer biochemical relapse. Most patients with Paget's disease will probably need such treatment only once.